Designing a NiFe-LDH/MnO2 heterojunction to improve the photocatalytic activity for NOx removal under visible light - Oliva Lamarca, María Angeles; Giraldo García, David; Almodóvar Losada, Paloma; Martín-Jiménez, Francisco de Paula; López, María Luisa; Pavlovic Milicevic, Ivana; Sánchez-Granados, Luis (Elselvier, 2024)
2D/2D heterojunctions between ultrathin NiFe-CO3 layered double hydroxide (LDH) and varying amounts of birnessite (δ-MnO2) were prepared using an environmentally friendly and cost-effective self-assembly method. The prepared samples have proven to be efficient in their application, mitigating NOx emissions via a photooxidative process. The effective creation of 2D/2D NiFe–LDH/MnO2 heterojunctions has been verified through a variety of characterisation techniques, such as XRD, FT-IR, TGA, XFR, N2 adsorption–desorption isotherms, HRTEM and SEM images, EDX, and XPS. Photocatalytic measurements have indicated that the heterojunction formed between NiFe-LDH and MnO2 modifies its photoconductive behaviour, significantly enhancing the visible light photocatalytic performance of the partners. Finally, the optimal relationship between NiFe-LDH and MnO2 in the photocatalytic process was studied. It was found that a ratio of 10:1, respectively, exhibited superior properties compared to the other composites, highlighting the best performance in the degradation of NO under visible light and notable stability during the recycling process.
Keywords: Óxidos de nitrógeno; LDH; Birnessite; Heterojunction; Photocatalysis; Nitrogen oxides; Depollution